The Bibliometric Analysis of Biofuel–Gasoline Research on Emission Performance and Material Durability in Combustion Systems - Lubis, Putri Bintang; Najiha, Putri; Pramana, Yoddis (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2026)
This study aims to analyze the research development on biofuel–gasoline blends, focusing on emission performance and material durability within combustion systems through a bibliometric approach. Data were retrieved from the Scopus database covering the period 2022–2026, including 1,746 English-language documents in the Engineering subject area. The analysis was conducted using VOSviewer software to map publication trends, research themes, and author collaboration networks. The results show an increasing trend in publications from 2022 to 2025, indicating growing scientific interest in energy efficiency and carbon emission reduction. The thematic map identified four major clusters, with dominant themes such as biofuel, carbon dioxide, and life cycle, reflecting a shift in research orientation toward sustainable energy systems. Furthermore, the co-authorship network revealed strong collaborative links among researchers, particularly from Asian countries such as China and India. Overall, this study highlights that research on biofuel–gasoline blends is evolving toward a globalized and sustainability-oriented framework, emphasizing efficiency, material resilience, and low-emission combustion technologies in support of the global clean energy transition.